EFEKTIVITAS METODE TABARAK DALAM MENGHAFAL AL-QURAN ANAK USIA DINI DI TAHFIZH ANAK USIA DINI ( TAUD ) BUNAYYA SHOHIBUL QURAN PANDAI SIKEK - Lidya Oktaviani; Arifmiboy Arifmiboy; Iswantir M; Junaidi Junaidi (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by several factors that cause students' memorization to vry. As for the factors, namely the ability of memory and hearing ability of each child is different, the habits of early childhood who like to play and cannot focus during tahfizh lessons, use of inappropriate or inappropriate methods, lack of support from parents and lack of support from parents. the spirit of students in repeating memorization. This study aims to see how effective the use of the tabarak method is in memorizing the Koran for early childhood at TAUD Bunayya Shohibul Quran. This type of research is descriptive with a quantitative approach. The population in this study were all 60 students of TAUD Bunayya Shohibul Quran, while the sample was students who memorized chapter 30, namely 36 people with a random sampling technique. In analyzing the data, the researcher used the one sample T test. The results of this study indicate that the implementation of the tabarak method in TAUD Bunayya is effective. From hypothesis testing, it is found that Ha is rejected and Ho is accepted, namely the average value of memorizing early childhood students using the tabarak method is equal to 80. Keywords: Tabarak method, memorizing the Qur'an